Re-doped fullerene-like MoS2 nanoparticles in relationship with soft lubrication. Issue 1 (1st June 2015) - Kampf, N.; Lobik, L.; Goldbart, O.; Tenne, R.; Shay, B.; Shumalinsky, D.; Ron, R.; Yadgarov, L.; Wagner, H. D.; Rosentsveig, R.; Elianov, O.; Sedova, A.; et al.
Abstract : Inorganic, fullerene-like (IF) nanoparticles of tungsten disulfide (WS2 ) and molybdenum disulfide (MoS2 ) have been synthesised in the past and their useful tribological properties have been studied quite extensively. Rhenium doping of such nanoparticles was also reported and studied to some extent. Herein, further studies of the physico-chemical properties are reported in connection to lubrication under mild loads. Due to their self-repelling character, the doped nanoparticles form tessellated monolayers on certain substrates. When mixed in small amounts, the IF nanoparticles lead to a reduction in the viscosity of water-based gels. Furthermore, the added nanoparticles lead to a precipitous reduction in traction force (friction) under mild loads. The lubrication mechanism of such nanoparticles is briefly discussed.